Unraveling the influence of political marketing on electoral decision-making: A robust analysis with PLS-SEM - Jorge Alberto Vargas-Merino; Cristhina del Pilar Pillaca-Villarruel; Gian Pierre Silvera-Otañe; Gisela Analy Fernández-Hurtado; Luis Miguel Olórtegui-Alcalde; Alfredo Martín Berrospi-Ytahashi (Social Sciences and Humanities Open)
This study examines the impact of political marketing on electoral decisions, even when there is decisional conflict, highlighting its evolution towards more precise and integral communication strategies within political campaigns. Using a quantitative approach applying Partial Least Squares Structural Equation Modeling (PLS-SEM) and extracting information from 526 Peruvian voters. Through three questionnaires, the study explores the dimensions of political marketing, the complexities of electoral decision-making and the dynamics of decisional conflict. The B coefficients allowed us to measure the influence of the predictive variables on the dependent variables. Some hypotheses were validated; thus, it is concluded that political marketing has a strong influence (0.690∗∗∗) on the electoral decision and on decisional conflict (0.432∗∗∗). Political marketing constructs such as product, price, promotion, physical evidence and people significantly influence the electoral decision while processes and others were not tested. Finally, the electoral decision does influence decisional conflict (0.469∗∗∗). The R2 values for electoral decision (0.476) and decisional conflict (0.652) support the predictive ability of the model; together with the high global fit index (GoF) they reinforce the confirmation of the model's prediction and justify the postulated theories, while supporting the claim that political marketing strategies are indeed relevant for electoral decision making even in scenarios of conflict or uncertainty.